Optimal position collaborative control of dual permanent magnet synchronous motor system - Dewu Yi; Shun Lin; Zhiqiang Wang (Systems Science & Control Engineering)
In order to improve the control accuracy and synchronous performance of the multi-motor control system, this paper proposes an optimal position collaborative control strategy for dual permanent magnet synchronous motor system. Firstly, based on the mathematical model of permanent magnet synchronous motor, an incremental predictive model is established to suppress constant and slow time-varying disturbances caused by changes in rotational inertia and load torque. Afterwards, the predicted compensation amount after multi-step prediction is obtained by minimizing the cost function which contains the synchronous error and tracking error simultaneously, and compensated to the given current loop in advance without changing the original dual motor system structure. Then the controllability and observability of the system are analyzed, and it can be proved that the system is asymptotically stable based on the optimal control theory. Secondly, considering the constraints such as maximum voltage and current limits, the optimal solution under the constraints is output to obtain the reference currents iq1 and iq2. Finally, it is demonstrated through the experiments that the proposed control strategy can achieve advance prediction compensation control of synchronous error, and the dynamic response speed is improved, while ensuring its steady-state performance remains unchanged.